Language as a Catalyst for Shaping Religious Identity and Political Ideology in the Era of Social Media - Munibi, Ahmad Zaki (Jurnal Multidisiplin West Science, 2025)
Beyond its traditional communicative purpose, language in the digital era serves as a strategic mechanism for constructing public opinion, affirming group solidarity, and circulating ideological content. However, its usage on social media platforms frequently contributes to increased social polarization. This study investigates the role of language in influencing religious identity and political ideology within digital discourse, emphasizing its dual capacity to foster both social cohesion and division. A Systematic Literature Review was conducted, comprising 44 peer-reviewed articles indexed in Scopus and Web of Science, published between 2021 and 2025. The analysis reveals a range of linguistic strategies, including symbolic representations, emotional rhetoric, and ideological framing, all of which play a significant role in constructing group identity and solidarity, while simultaneously intensifying societal fragmentation. These findings are interpreted through the lens of Critical Discourse Analysis and Framing Theory. The study highlights the urgent need for stronger regulatory frameworks addressing extremist content and calls for enhanced digital literacy to foster more responsible engagement in online discourse. Furthermore, it recommends future research to examine language use in non-English-speaking communities and to explore the long-term implications of digital communication on identity construction. This research contributes to a deeper understanding of the complex interplay between language, ideology, and identity in contemporary digital environments.